Spray deposition on weeds of common bean crops - Rodrigues-Costa, Andreia C. P.; Martins, Dagoberto [UNESP]; Costa, Neumarcio V.; Pereira, Maria R. R. [UNESP] (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2011)
A.C.P. Rodrigues-Costa, D. Martins, N.V. Costa, and M.R.R. Pereira. 2011. Spray deposition on weeds of common bean crops. Cien. Inv. Agr. 38(3): 357-365. Weed control failure in common bean (Phaseolus vulgaris L.) production may be related to inappropriate herbicide application techniques. The purpose of this study, therefore, was to evaluate the amount of spray solution deposition that occurred on the weeds, Bidens pilosa L. and Brachiaria plantaginea (Link) Hitch., both within and between rows of common beans. The research was arranged in a randomized block design with four replications. The following 6 spray nozzles were used: flat fan nozzles XR 110015 VS (150 L ha(-1)) and XR 11002 VS (200 L ha(-1)); cone nozzles TX VK 6 (150 L ha(-1)) and TX VK 8 (200 L ha(-1)); and twin flat fan nozzles TJ60 11002 VS (150 L ha(-1)) and TJ60 11002 VS (200 L ha-1). The results showed that the loss of the spray solution on the soil occurred mainly within the bean rows and with a high intensity when using a nozzle spraying 200 L ha(-1). At 30 days after sowing, the TX (150 L ha(-1)) nozzle was the only nozzle that promoted deposits of less than 210.0 mu L g(-1) of dry mass. The spray nozzles showed a good performance in the deposition of the spray solution on the weeds that occurred both within and between the rows. However, for both species there was great variation in individual deposits depending on their location in relationship to the plants.

Los fracasos en el control de malezas en frijol (Phaseolus vulgaris L.) pueden estar relacionados con inadecuadas técnicas de aplicación de herbicidas. Se determinó la cantidad de deposición de las gotas de pulverización en las plantas de Bidens pilosa L. y Brachiaria plantaginea (Link) Hitch., presentes en la línea y entre la línea de frijol. Se evaluaron 6 boquillas de pulverización: de abanico plano XR 110.015 (150 L ha-1) y XR 11002 VS (200 L ha-1), de cono TX VK 6 (150 L ha-1) y TX VK 8 (200 L ha-1) y de doble abanico plano TJ60 11002 VS (150 L ha-1) y TJ60 11002 VS (200 L ha-1). Se utilizó un diseño de bloques al azar con 4 repeticiones. Los resultados mostraron que la pérdida de caldo al suelo se produjo principalmente en las líneas de frijol y con mayor intensidad con el uso de volumen de aplicación de 200 L ha-1. A los 30 días post siembra del frijol, la boquilla TX (150 L ha-1) fue el único tratamiento que promovió depósitos menores a 210,0 μL g-1 de materia seca. Las boquillas de pulverización evaluadas mostraron un buen desempeño en la deposición de gotas en la maleza B. pilosa y B. plantaginea presentes en la línea y en la entre línea. Sin embargo, existió una gran variación en los depósitos individuales de ambas especies según su ubicación en relación al cultivo.
Depósitos de las gotas de pulverización sobre las malezas en frijol
Keywords: Application technology; Bidens pilosa; Brachiaria plantaginea; nozzle; Phaseolus vulgaris